Performance analysis of cognitive hybrid radio frequency and free space optical cooperative networks. (May 2022) - Qin, Dong
Abstract: This paper studies the exact performance of hybrid radio frequency and free space optical cooperative amplify and forward communication networks in a cognitive radio environment, where secondary users cannot transmit signals at any power level since the existence of the primary users restrict the behavior of the secondary users within an acceptable and reasonable range. In particular, a secondary relay station connects a destination through a free space optical link, whose random characteristics follows a widely used gamma–gamma fading distribution with non zero pointing error to characterize the assignable effects of atmospheric turbulence. Different from the traditional analysis methods in probability theory based on cumulative distribution function or outage probability, the complicated integral domain division is avoided by virtue of the moment generating function of reciprocal signal to noise ratio. Under the maximum interference level constraint of the primary user, exact closed form expressions of moments of signal to noise ratio, ergodic capacity, higher order statistics of the capacity, and average bit error probability are derived naturally. Finally, simulation results are provided to flawlessly demonstrate the theoretical analysis. Graphical abstract: Highlights: The precise performance analysis of hybrid radio frequency and free space optical communication systems is presented. The moment generating function of the reciprocal signal to noise ratio is used. The secondary relay station is assumed to suffer from the interference of the cochannel signals.